90-degree impact bench test and simulation analysis of automotive steel wheel. (November 2019) - Gao, Qian; Shan, Yingchun; Wan, Xiaofei; Feng, Qizhang; Liu, Xiandong
Abstract: As one of the important components affecting the safety and reliability of automobile, the wheel needs to meet the test requirements for fatigue and impact performance. The 90-degree impact test of wheel is used to replicate the harsh conditions during driving, such as automobile frontally impact on road pits. In order to guarantee the performance of wheel, many automobile companies have begun to increase impact performance requirements on steel wheels, although there is no public standard for 90-degree impact test of steel wheel. In this paper, the FE model of wheel assembled composite tire are established first, and then used to evaluate the impact resistance of wheel. Furthermore, two different test benches and two different tires are modeled to investigate the effects of test methods and tire sizes on the wheel performance evaluation results. To evaluate the validity of the simulation method, the wheel 90° impact tests with different tires are also performed. The comparison between the simulation and test results show that the simulation methods presented in this paper can provide an effective way to evaluate the impact resistance of the wheel, and the influences of different tires should be fully considered in the wheel 90-degree impact test. Highlights: Simulation results of the 90° impact test of steel wheel verified by experimental results. Investigating the effects of test methods and tire sizes on the simulation results. Disclosing the dual effects of tire brand and size on wheel performance.